Incentives-based hierarchical demand response program (2017)
"A novel hierarchical demand response program is presented. It takes into account the customers' energy consumption preferences in an environment with smart-autonomous loads and appliances. Energy consumption activities are defined as coalitions of loads with a value that represent their compactness and importance for the user and the Shapley value allows to reduce the size or a coalition reducing the energy consumption according to the user' consumption strategy. The demand side is divided in three levels: (i) electricity market level; (ii) customer's level; and (iii) loads level. For each level, a game-theoretical framework is developed to achieve an optimal energy allocation in a decentralized way. An incentives scheme is proposed for an electricity market with participative customers. The induce game is simulated in order to verify the efficiency and the reduction or the peak to average ratio "'hen the equilibrium of the game is implemented". Tomado del Abstract